PENGARUH MODEL PEMBELAJARAN COOPERATIVE TIPE MAKE A MATCH TERHADAP MOTIVASI BELAJAR - Muh Syihab Ikbal; Muhammad Qaddafi; Hasninda (JPF (Jurnal Pendidikan Fisika) Universitas Islam Negeri Alauddin Makassar, 2022)
This study aims to determine the effect of the cooperative learning model of the make a match type on the students' motivation to learn physics. The research design used was the matching only post-test control group design. The population of this study were all students of class X MIPA SMA Negeri 6 Wajo, totaling 117 people. A sample of 42 people was obtained by using a two-step matching sampling technique. The results of this study indicate that: 1) the students' motivation to learn physics who are taught using the make a match type of cooperative learning model is categorized as high; 2) the motivation to learn physics of students who are taught using conventional learning models is categorized as high; 3) There is no difference in the motivation to learn physics between students who are taught with the make a match type of cooperative learning model and the conventional learning model. However, both learning models are able to have a good impact on students' motivation to learn physics, as seen in the category of learning motivation that students have at a high level.